Studying the Photodegradation of Congo Red Dye from Aqueous Solutions Using Bimetallic Au–Pd/TiO2 Photocatalyst (Baghdad Science Journal, 2021)
In this study, the photodegradation of Congo red dye (CR) in aqueous solution was investigated using Au-Pd/TiO2 as photocatalyst. The concentration of dye, dosage of photocatalyst, amount of H2O2, pH of the medium and temperature were examined to find the optimum values of these parameters. It has been found that 28 ppm was the best dye concentration. The optimum amount of photocatalyst was 0.09 g/75 mL of dye solution when the degradation percent was ~ 96 % after irradiation time of 12 hours, while the best amount of hydrogen peroxide was 7μl/75 mL of dye solution at degradation percent ~97 % after irradiation time of 10 hours, whereas pH 5 was the best value to carry out the reaction at the highest degradation percent. In addition, temperature tested at range of (25-55) C˚, and it has been figured out which photodegradation percent of dye increase with raising temperature (degradation percent was ~ 98% after irradiation time of 4 hours at 55 C˚), and the activation energy of the reaction was calculated (34.8016 kJ/mole) from Arrhenius law. The thermodynamic functions ΔH#, ΔG#, and ΔS# were obtained, where ΔH# and ΔG# are positive value which means that the reaction is endothermic and non-spontaneous respectively, while ΔS# has a negative value, thus indicates that the reactants are more disordered than the excited intermediate formed. The kinetic of the reaction was studied, and it has been found that the photocatalytic reaction follows pseudo first order reaction.